Determinants of Managerial Preventive Actions in Relation to Common Mental Disorders at Work: A Cross-Sectional Study Among Swedish Managers. Issue 10 (October 2019) - van de Voort, Iris; de Rijk, Angelique; Hensing, Gunnel; Bertilsson, Monica
Abstract : Objective: Manager characteristics (personal, work-, and competence-related) were investigated as determinants of managerial preventive actions (MPAs) in relation to common mental disorders (CMDs) among employees. Methods: A web survey ( n  = 2921) among Swedish managers measured diverse managerial characteristics and two types of MPAs: reviewing assignments and work situation (MPA-review); talking about CMDs at the work place (MPA-talk). Results: MPA-review was reported by 50% and MPA-talk by 57% of managers. Characteristics that related to more MPAs were female gender, workplace offering lectures on CMDs, workplace offering stress counseling, being responsible for the work environment, management training on CMDs, and more than 10 years of managerial experience (MPA-talk only). Conclusion: Managers who are female, have had training on CMDs, and work for organizations paying attention to CMD prevention initiate MPAs more often.